Contaminant profiles of air and soil around Casey station, Antarctica; Discerning local and distant contaminant sources - Bengtson Nash, Susan; Xiao, H; Schlabach, Martin; Stark, J; King, C; Hung, H (Society for Environmental Toxicology and Chemistry (SETAC), Europe 21st Annual Meeting. Ecosystem Protection in a Sustainable World: A Challenge for Science and Regulation, 2011)
The primary input of Persistent Organic Pollutant (POP) contamination to the Antarctic is expected to be via Long Range Atmospheric Transport (LRAT) from emissions in neighboring Southern hemisphere nations In addition to LRAT, system input of POPs must increasingly consider alternate pathways Human activity in the Antarctic represents a potential direct source of both legacy and current-use chemicals It has been two decades since the organic chemical composition of air masses arriving in the Australian Antarctic Territory (AAT), which spans the majority of the eastern Antarctic sector, was last investigated Here we present the first atmospheric measurements made as part of a new continuous monitoring effort at Casey station (66°17’ S 110°31’ E), one of Australia’s all-year research stations The results are evaluated alongside POP contamination data of soil samples collected around the Casey station perimeter and the respective sample profiles are assessed for clues as to local and distant contamination sources Results suggest a potential local source of the currently produced, involatile, deca-brominated PBDE congener 209 which contributed substantially to PBDE profiles of all samples Profiles of polychlorinated biphenyls (PCBs) and rganochlorine pesticides on the other hand primarilly support LRAT as the primary input pathway of these contaminants, whilst a dominance of endosulfan in air samples evidences its ongoing application in the southern hemisphere.
Keywords: Antarktis; atmosfæren; forskningsstasjoner; forurensning; miljøgifter

Learning from the Antarctic whaling : report and proceedings - Walløe, Lars; Barthelmess, Klaus; Gambell, Ray; Ohsumi, Seiji; Komatsu, Masayuki (International Symposium Commemorating Centennial of the Antarctic Whaling, 2005)
Keywords: Antarktis; Sørishavet; historie; hvalfangstindustri; hvalindustri; pelagisk

Ozone loss rates over the Arctic 2002/03 and Antarctic 2003 measured with the Match approach - Streibel, Martin; von der Gathen, P; Rex, M; Deckelmann, H; Harris, N; Braathen, G; Chipperfield, M; Millard, G; Reimer, E; Alfier, R; Allaart, M; Andersen, S; et al. (20th Quadrennial Ozone Symposium, 2004)
To improve our understanding of wintertime polar ozone losses, two ozonesonde Match campaigns were performed. The first one was carried out in the Arctic winter 2002/03. About 450 coordinated ozonesondes were launched from late November 2002 to March 2003. Temperatures low enough for the formation of polar stratospheric clouds (PSC) occurred already in the second half of November. At 475 K the Match analysis shows increasing ozone loss rates from early December until the second half of January with peaking loss rates of 35 ppbv/day. Afterwards the rate of ozone loss decreased and stopped after a month. Throughout the whole winter we find accumulated ozone loss of about 1.5 ppmv at the 500 K isentrope and approximately 60 DU in the total ozone column, which is about half of the maximum loss found in past winters. From June to October 2003 an Antarctic Match campaign was carried out for the first time. About 400 sondes were launched by 9 stations. Ozone loss rates of up to 75 ppbv/day were found inside the polar vortex at the 475 K potential temperature level during the first half of September. The timing of the fastest ozone loss coincides with the return of sunlight to the vortex after the Antarctic winter. During the whole time period temperatures were low enough for PSCs, including ice clouds, to form. Results for the potential temperature range between 400 K and 550 K will be presented.
Keywords: Antarktis; ozonlaget; polarområdene; stratosfæren

Accumulation of heavy metals in an Antarctic food-chain - Lie, Elisabeth; Steinnes, Eiliv ("Heavy metals in the environment", 10th International Conference, 1995)
Keywords: Antarktis; forurensning; miljøgifter; næringskjede

Environmental radioactivity in the Arctic and Antarctic - Holm, Elis (red.); Strand, Per (red.) ("International Conference on Environmental Radioactivity in the Artic and Antarctic organized by Norwegian Radiation Protection Authority, Norway and Department of Radiation Physics, Lund University, Sweden., 1993)
Keywords: Antarktis; miljøforurensing; polarområdene; radioaktivitet

Geology and petrology of the Southern Heritage Range, Ellsworth Mountains - Hjelle, Audun; Ohta, Yoshihide; Winsnes, Thore S. (Antarctic geoscience, 1982)
Paper No. 74
Keywords: Antarktis; ekspedisjoner; geologi; petrologi

Antarctic resources: report form the informal meeting of experts 30 May - 9 June 1973 (Antarctic resources, 1973)
Keywords: Antarktis; forskning; jus; politikk; ressurser

Some features of the turbulence over a snow field - Vinje, Torgny E (Polar meteorology : WMO/SCAR/ICPM symposium on polar meteorology, 1967)
Keywords: Antarktis; meteorologi